Design and optimization of dual-cycled cooling structure for fully-enclosed permanent magnet motor. (April 2019) - Chen, Wei; Ju, Yuning; Yan, Dong; Guo, Liyan; Geng, Qiang; Shi, Tingna
Highlights: A novel dual-cycled cooling structure for fully-enclosed permanent magnet motor is designed. Obviously suppressing the temperature rise of the rotor and the permanent magnets. The temperature of the motor is analyzed by numerical analysis. The motor with proposed cooling structure still has good electromagnetic performance. Abstract: For fully-enclosed permanent magnet motor (FEPM), the heat generated inside the rotor is difficult to dissipate, which can deteriorate the function of the permanent magnet and cause the motor performance degradation, especially during the field-weakening operation. A dual-cycled cooling structure is proposed for improving the inner heat transfer condition of the FEPM, which uses outer water and inner air as coolants. The 3D model of the FEPM equipped with water jacket is built and the temperature distribution is analyzed by thermal-fluid numerical analysis and its accuracy is verified by experiments. Based on the results, the rotor axial vent hole (RAVH), stator axial vent hole (SAVH) and air gap are chosen as internal cycled paths. The position of the internal cycled path is set according to the electromagnetic analysis. And the dimension of the internal cycled path is optimized by Taguchi method for better cooling effects which are evaluated through fluid-thermal coupled numerical analysis. The final optimization results indicate that the optimal dual-cycled cooling structure can reduce the maximum temperature inside the motor by 13.5 °C, which will suppress the internal temperature and improve the reliability of the FEPM in full operating range.